Health Care Experiences of Lesbian Women: A Metasynthesis. (January 2019) - Snyder, Marianne
Abstract : Lesbian women experience discrimination within the health care system that leads many to cautiously navigate a heteronormative system. This metasynthesis offers a richer contextual understanding about lesbian health care experiences. The 4 overarching themes that emerged are: ( a ) sizing up the provider and the environment, ( b ) to say or not to say: "paradoxes of disclosure, " ( c ) reactions to provider's assumptions, ( d ) and acknowledging my partner. Lesbian women perceive their health care experiences based on the nature of the relationship with the provider. These women are more likely to seek care from health care providers who acknowledge, affirm, and respect a woman's sexual identity, cultural beliefs, and family structures.